2023
DOI: 10.3390/ijerph20085539
|View full text |Cite
|
Sign up to set email alerts
|

Compound Heat Vulnerability in the Record-Breaking Hot Summer of 2022 over the Yangtze River Delta Region

Abstract: Hourly meteorological data and multisource socioeconomic data collected in the Yangtze River Delta (YRD) region were used to analyze its heat vulnerability during the record-breaking hot summer of 2022 in both daytime and nighttime. Over forty consecutive days, daytime temperatures exceeded 40 °C, and 58.4% of the YRD region experienced 400 h with temperatures hotter than 26 °C during the nighttime. Only 7.5% of the YRD region was under low heat risk during both daytime and nighttime. Strong heat risk combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
(54 reference statements)
0
0
0
Order By: Relevance
“…Additionally, research is needed to examine heat vulnerability spatiotemporal characteristics-particularly, diurnal and nocturnal differences. While analyses almost exclusively gauge daytime heat risk, a recent study found the ratio of susceptible urban areas is higher at night [84]. Moreover, diurnal/nocturnal heat exposure patterns vary, and some studies found stronger UHI during nighttime [30,85,86].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, research is needed to examine heat vulnerability spatiotemporal characteristics-particularly, diurnal and nocturnal differences. While analyses almost exclusively gauge daytime heat risk, a recent study found the ratio of susceptible urban areas is higher at night [84]. Moreover, diurnal/nocturnal heat exposure patterns vary, and some studies found stronger UHI during nighttime [30,85,86].…”
Section: Discussionmentioning
confidence: 99%